The effect of white collar crime announcement on stock price performance : Evidence from Malaysian stock market - Tay, Liangmui; Puah, Chin Hong; Brahmana, Rayenda Khresna; Malek, Nurul Izza Abdul (Emerald Group Publishing Ltd, 2016)
Purpose - The purpose of this paper is to investigate the connection between ethics and profitability by examining the association between published reports on white-collar crime and the share-price performance of the Malaysian-listed companies. This study aims to examine the role of white-collar crime in Malaysian-listed companies on its stock-price reaction. Design/methodology/approach - Following prior research, even study methodology is used to exploit the stock-price reaction on the white-collar crime announcement. The daily bases of average abnormal returns (AARs) and cumulative average abnormal returns (CAARs) with an event window of 90 days prior to and after the announcements are determined. This study uses public announcement data of white-collar crimes from Malaysian Securities Commission from 1996 to 2013. Findings - The finding indicates that an announcement of a white-collar crime has a negative abnormal return on the share price. As a result, the market does not react efficiently toward the information released regarding the incidence of a white-collar crime. Practical implications - This study contributes to the managerial decision theory, where managers should be able to see a definite connection between unethical behavior and their firm's stock. The stockholders and policymakers should find this information important in pressing for greater corporate and managerial accountability. Originality/value - Unlike prior research, this paper investigates the stock-price performance due to white-collar crime announcement in the Malaysian context by using complete data set of announcement from 1996 to 2013.